NEW STABILITY-INDICATING ULTRA PERFORMANCE LIQUID CHROMATOGRAPHY METHOD DEVELOPMENT AND VALIDATION OF LENVATINIB MESYLATE IN BULK DRUG AND PHARMACEUTICAL DOSAGE FORMS - Bandla, Jahnavi; Ganapaty, S. (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the present study was to develop and validate a new stability-indicating method for the quantification of lenvatinib mesylate in bulk drug and pharmaceutical dosage form using ultra performance liquid chromatography (UPLC). Methods: The optimized chromatographic conditions for elution of drug included UPLC HSS C18 (100 mm × 2.1 mm, 1.8 m) column, mixture of 0.1% orthophosphoric acid and acetonitrile (50:50 v/v%) mobile phase run on an isocratic mode at a flow rate of 0.3 mL/min, 240 nm detection wavelength, and column oven temperature maintained at 30°C. Results: The retention time for lenvatinib was found to be 1.24 min. The developed method was validated for various validation parameters in accordance with the International Conference on Harmonization guidelines. The method obeyed Beer's law in the concentration range of 2.5– 15 μg/mL with a correlation coefficient of 0.9996. The percentage relative standard deviation and percentage recovery were determined to be 0.4 and 99.66–100.30%, respectively. The developed method was found to be accurate, precise, specific, linear, rugged, and robust. Forced degradation studies were conducted by exposing the drug to diverse stress conditions such as acidic, basic, peroxide, neutral, photolytic, and thermal conditions. The net degradation was obtained within the limits. Conclusion: The developed method for the estimation of lenvatinib can be employed to routine analysis of pharmaceutical dosage form.